Structural performances, thermal insulating and fire resisting abilities of rubberized concrete wall panel utilizing magnesium oxide board as the skin layer - Mok, Shao Jun (2023)
The dramatic increase of waste tyres and rubber wastes has become a global environmental issue due to the rapid growth of the automobile industry. Further, population growth and urbanisation create a massive demand for raw construction materials. Over the past few decades, multiple researchers have distinguished the possibilities to utilise rubber waste and create its second value, such as partially replacing aggregates with rubber particles to produce rubberized concrete and apply it in the construction industry. Hence, this study aims to investigate the engineering properties of rubberized lightweight foamed concrete (RLFC) sandwiched wall panels. Flexural strength test, compressive strength test, thermal conductivity test, and flame exposure tests were conducted to determine the performance of rubberized lightweight foamed concrete (RLFC) sandwiched wall panels. The RLFC sandwiched wall panels were cast with RLFC inner core layer and magnesium oxide board as the skin layers. The inner core is produced by mixing foam and crumb rubber with concrete. Three different thicknesses of magnesium oxide board specimens were prepared, namely, 6MGO (6 mm), 9MGO (9 mm), and 12MGO (12 mm), respectively. All achieved a target density of 1150 kg/m3 and an inner core thickness of 105 mm. Based on the results from lab experiments and the comparison between 6MGO and 12MGO, the changes in percentage for ultimate flexural strength and thermal conductivity are +24.05 % (18.13 kN to 22.49 kN) and -7.19 % (0.3904 Wm-1K -1 to 0.3642 Wm-1K -1 ) respectively when the thickness of skin layer increase from 6 mm to 12 mm. Besides, no cracking or damage was found on the skin layer after exposure to direct flame for 60 minutes. The connection between both specimens' inner core and skin layer was in good condition. Based on the result, it can be concluded that the magnesium oxide board is suited as the skin layer of the RLFC sandwiched wall panel. According to the thermal insulation and fire-resisting performance, the sandwiched wall panel produced from this study may be ideally applied as a non-load-bearing wall system in the construction industry to reduce the effect of rubber waste on the environment. Further studies are needed to compare the results obtained from this study by using various types of sheathing material as skin layer and different mix proportions to cast the inner core.